2014
DOI: 10.1037/lhb0000063
|View full text |Cite
|
Sign up to set email alerts
|

Field reliability of the Psychopathy Checklist-Revised among life sentenced prisoners in Sweden.

Abstract: Although typically described as reliable and valid, the Psychopathy Checklist-Revised (PCL-R) has come under some criticism by researchers in the last half-decade due to evidence of poor interrater reliability and adversarial allegiance being reported in applied settings in North America. This study examines the field reliability of the PCL-R using a naturalistic test-retest design among a sample of Swedish life sentenced prisoners (N = 27) who had repeatedly been assessed as part of their application to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 54 publications
(110 reference statements)
10
35
4
Order By: Relevance
“…Most earlier field studies have been based on SVP cases, raising questions as to whether the poor reliability of forensic examiners in these cases perhaps might be associated with something unique or at least atypical about sexual offenders or the process of per forming PCL-R evaluations in these types of civil commitment cases . Our data suggest, however, that the poor field reliability of the PCL-R scores in these cases does not appear to be specific to the assessment of sexual offenders, which is generally consistent with the lower reliability results from one earlier small-scale Swedish field study that involved teams of raters (Sturup et al, 2014). As such, the differences we obtained offer little support for the position that forensic examiners' PCL-R scores might be more reliable in other types of cases, given that the ICC values actually were lower overall in cases not involving sex crimes.…”
Section: Discussionsupporting
confidence: 85%
“…Most earlier field studies have been based on SVP cases, raising questions as to whether the poor reliability of forensic examiners in these cases perhaps might be associated with something unique or at least atypical about sexual offenders or the process of per forming PCL-R evaluations in these types of civil commitment cases . Our data suggest, however, that the poor field reliability of the PCL-R scores in these cases does not appear to be specific to the assessment of sexual offenders, which is generally consistent with the lower reliability results from one earlier small-scale Swedish field study that involved teams of raters (Sturup et al, 2014). As such, the differences we obtained offer little support for the position that forensic examiners' PCL-R scores might be more reliable in other types of cases, given that the ICC values actually were lower overall in cases not involving sex crimes.…”
Section: Discussionsupporting
confidence: 85%
“…4 Even studies that purport to find questionable field reliability of psychopathy measures nevertheless show significant agreement in assessments of psychopathic offenders. A recent study of life sentenced inmates in Sweden, for instance, reported significant intraclass correlations for PCL-R total scores and scores on Factor 1 and Factor 2 (Sturup et al, 2013). In addition, assessments of the antisocial features of psychopathy (Facet 4 in the PCL-R) had an intraclass correlation of .90.…”
Section: Potential Integration and Discussionmentioning
confidence: 94%
“…Swedish law has a long tradition of responding to criminal behaviour by imposing individual, rehabilitating sanctions, not least forensic psychiatric care. The proportion of people with a non‐psychotic mental disorder, who are given a hospital order after a criminal offence, is higher compared to many other countries (Sturup et al, ; Svennerlind et al, ; Sturup & Lindqvist, ).…”
Section: The Swedish Systemmentioning
confidence: 94%
“…Despite this, recidivism among homicide offenders remains under‐researched (Golenkov et al, ; Large et al, ). Moreover, research on the reliability and predictive validity of different risk assessments used with long‐term prisoners is scarce (Simourd, ; Sturup et al, ), and yet reliability and validity of instruments tested with individuals serving short‐term prison sentences do not necessarily transfer to their use with long‐term prisoners (Manchak et al, ). Some researchers have even suggested that the longer the time away from the rest of the society, the higher are the recidivism rates among homicide offenders (Baay et al, ).…”
mentioning
confidence: 99%